Расстройства углеводного обмена у детей: гипогликемия, гипергликемия - Чартаков А.К (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
The lecture describes types, causes, pathogenesis key components, manifestations of typical forms of carbohydrate metabolism pathology: hypoglycemia, hyperglycemia, glycogenosis, aglycogenosis, hexosemia. A case problem and multiple choice tests are given.